ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PAJAK HOTEL DAN RESTORAN (Studi Empiris di Daerah Pantai Utara Jawa Bagian Barat Provinsi Jawa Tengah Tahun 2003-2012) (Students' Journal of Accounting and Banking, 2014)
The purpose of this study was to analyze the influence of the number of hotels, occupancy rates, inflation, GDP, and the number of tourists as a factor affecting the Hotel and Restaurant Tax receipts in the west coast of Central Java province. The data used are secondary data from the years 2003-2012 was obtained from the publication of the Central Statistics Agency (BPS), Central Java Province. The analytical tool used is regression analysis Regression methods and descriptive study.The population used in this study is the data Tax Regency Hotel and Restaurant in Central Java city of which includes data Number of Hotels, Hotel Room Occupancy Rate, Inflation Data, Data GDP and data on the number of tourists visiting the District / City West area of the northern coast of Central Java province. As for the samples in this study using existing data availability is data in Hotel and Restaurant Tax Pantura Region West Central Java province during the years 2003-2012.The results showed that the number of the hotel, room occupancy rate and a significant number of tourists has a positive effect on α <5 percent of the tax revenue hotels and restaurants, while the significant negative impact GDP and the inflation rate has no effect on actual revenues pajk hotel and restaurant.Keywords: Hotel and Restaurant Tax, Total Hotel Room Occupancy Rate, Inflation, GDP, The number of tourists, Central Java Province